Exploring Challenges and Strategies in TOEFL Preparation among Students at Universitas Muhammadiyah Aceh - Sarair, Sarair; Farsia, Lina; Irnanda, Septhia; Romi, Fadhlullah (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
In this descriptive quantitative study, thirty students from Universitas Muhammadiyah Aceh discuss the difficulties they had and the methods they used to get ready for the TOEFL. An 18-item questionnaire was used to gather the data, and the results show that the listening section presented the biggest issue, with 58.1% of participants finding it difficult to stay focused and limited in time. The reading portion, on the other hand, was thought to be easier, while some participants had trouble with vocabulary and time management. Students' strategies included using internet resources, with a significant emphasis on cognitive and metacognitive skills, such as TikTok, YouTube, and TOEFL-specific apps. Notably, frequent strategies for navigating the written expression and test structure parts included determining the core concept and closely examining sentence structure. These results imply that more students could benefit from focused listening exercises, improved training in metacognitive strategies, and expanded usage of online resources for TOEFL preparation. In order to better prepare students for the exam, educators might consider incorporating real TOEFL-like materials and time management advice into the curriculum.